Crescimento e fenologia de Araucaria angustifolia (Bertol.) Kuntze em três cotas de um gradiente de altitude na serra da Mantiqueira - Ribeiro, Suelen Francisca (2017)
The altitudinal gradient synthetizes environmental variations which can occur along latitudinal gradients and promotes differentiation in structure, ecological processes and species distribution. Studies in such environments can allow us to make inferences about plant responses to shifts in both micro and macroclimatic environmental conditions. Therefore, this study aimed to assess the radial growth and reproductive phenological responses of Araucaria angustifolia (Bertol.) Kuntze in relation to gradient elevation. For such, gradients at the Private Natural Heritage Reserve (RPPN) Alto-Montana, located at the Mantiqueira Range were chosen. During 28 months, 58 Araucaria angustifolia individuals were observed, distributed in three subpopulations situated at the elevations of 2000m, 1700m and 1540m along the RPPN. Manufactured dendrometers were installed for radial growth analysis and measures were carried out monthly. For phenology, reproductive structures sprouting from 60 A. angustifolia individuals were observed during 12 months at the correspondent elevations. Temperature, moisture, precipitation, global radiation, insolation, vapor-pressure deficit (DPV) and soil water holding capacity data as well as observations concerning competition were analyzed in order to interpret the growth responses to elevation. The gradients were distinctively characterized by the temperature, radiation, moisture and DPV variables, whereas water holding capacity was similar along the areas. Differences in reproductive phenology turned out to be inconclusive as compared to environmental data. Araucarias growth pace in the three gradients was not distinct, although the growth reconstruction indicates older, slower-growing trees at the 2000m elevation.